Knowledge disagreement formulations in problem-based learning tutorials: balancing pedagogical demands with 'saving face'. Issue 3 (2nd September 2018) - McQuade, Robert; Wiggins, Sally; Ventura-Medina, Esther; Anderson, Tony
ABSTRACT: As a pedagogical approach that aims to develop students' group-working skills and to challenge their current knowledge, problem-based learning (PBL) provides a unique setting in which to examine disagreements in interaction. Previous research on disagreements in classrooms has typically examined tutor–student interaction or student–student interaction in which a tutor is present. This paper, however, examines tutorless PBL tutorials and focuses specifically on those moments in which knowledge claims are challenged by other students. The data comprise 30 h of video recordings from 24 chemical engineering PBL tutorials in a Scottish university. Conversation analysis was used to identify 101 disagreement formulations, many of which follow the format seen in other classroom settings (e.g. agreement-prefaced disagreements). A subset of disagreement formulations manage epistemic responsibility through invoking expert sources (e.g. tutor-provided worksheets and academically superior out-group members). Through invoking an expert source in this way, students attend to the pedagogical activities – without tutor assistance – while minimising the conversational trouble associated with the act of 'doing' disagreement (i.e. indirectly enacting disagreements whilst maintaining a neutral stance). This paper thus contributes to CA literature on disagreements, while providing a unique insight into PBL tutorial interaction. Directions for future research are suggested.